Legitimacy, Regionalism, and Efficacy: Algeria’s Role in Modern West African Security Dilemmas - Naili, Meriem; Wittemyer, Sophia (Journal of Central and Eastern European African Studies, 2025)
This paper examines Algeria’s role in shaping regional dynamics through its relationships with two key actors in West Africa: the Polisario Front in Western Sahara and Niger’s junta government following the 2023 coup. It investigates how Algeria navigates its foreign policy to influence stability, with a focus on the concept of perceived legitimacy. Algeria’s support for the Polisario Front and diplomatic engagement with Niger’s coup leaders reflect its commitment to sovereignty, non-interference, and Pan-Africanism. By rejecting certain international recognitions, Algeria plays a significant role in shaping the regional security environment. It positions itself as a defender of self-determination and a protector of weaker states, offering diplomatic and military support to build regional alliances and counter external powers. This strategy contrasts with interventionist approaches, focusing instead on solidarity and regional cooperation. The paper argues that Algeria’s policy of non-interference, combined with its emphasis on legitimacy, contributes to both internal political stability in neighboring countries and broader security in Africa. It suggests that Algeria may be positioning itself as a regional superpower, with a long-term strategy to foster stability and strengthen its geopolitical influence. This study provides insights into how Algeria’s foreign policy shapes the broader security context in West Africa.